PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERTUKAR PASANGAN UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS III SD NEGERI 110 PEKANBARU - Rosni Yenti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The purpose of this study is to improve learning outcomes and activities of third grade students of SD Negeri 110 Pekanbarubecause the score was still below maximum exhaustiveness criteria that is determined above 70. This type of research isclassroom action research using a method of exchanging pairs in PKN subjects. The study was conducted in 2 cycles. Eachcycle consists of 2 activities. The outcomes of the first cycle about teacher activity is 12 which is criteria are not perfect, andactivity 2 (15 is quite perfect), the average score is 14 with a rating that is quite perfect. Cycle II, in activity one is 19 (veryperfect), the second meeting was 24, and the average number was 22 with very perfect criteria. Student activity at meeting 1was 93 (19 is low), activity 2 is 120 (24 criteria high) on average 107 criteria is high. Student activity in cycle II meetings forcycle 1 was 141 (28 with high criteria, 2nd cycle meeting rose to 169/34 and an average of 155 (31 with very high predicate.While learning outcomes in first cycle 1 93 (19) low criteria second meeting 120 (24) high criteria and an average of 107(21) high criteria, while the second cycle meeting 1 is 131 (28) high criteria, the second meeting 169 (34) was very high, sothe average cycle II is 155 (31) high.